2008
DOI: 10.1007/s00024-008-0426-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of the Destructive Meteotsunami of 15 June, 2006 on the Coast of the Balearic Islands

Abstract: A destructive tsunami-like event (locally known as ''rissaga'' waves) occurring on 15 June, 2006 in Ciutadella Harbour (Menorca, Balearic Islands) is reproduced by a numerical model forced by a travelling atmospheric disturbance. The disturbance is reconstructed from microbarograph measurements, being the only available instrumental data at the time of the event. The model is verified based on two weaker 1997 events, which were recorded by a number of bottom pressure recorders operating at that time on the Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 31 publications
(59 reference statements)
5
67
0
Order By: Relevance
“…the passage time of the disturbance over a fixed point) is small compared to the inertial period. V07 and V10 contributed to understanding how atmospheric disturbances of short time scales may excite shelf seiches and large transient waves which can result in destructive meteotsunami events (within the 5-30 min period band) at several locations around the world (Nomitsu 1935;Defant 1961;Monserrat, Ibbetson & Thorpe 1991;Rabinovich & Monserrat 1996;Monserrat, Vilibić & Rabinovich 2006;Vilibić et al 2008;Goring 2009). Here it is shown that conditions for the occurrence of Proudman resonance and that suggested by V10 are modified in the presence of Coriolis effects.…”
Section: Introductionmentioning
confidence: 83%
“…the passage time of the disturbance over a fixed point) is small compared to the inertial period. V07 and V10 contributed to understanding how atmospheric disturbances of short time scales may excite shelf seiches and large transient waves which can result in destructive meteotsunami events (within the 5-30 min period band) at several locations around the world (Nomitsu 1935;Defant 1961;Monserrat, Ibbetson & Thorpe 1991;Rabinovich & Monserrat 1996;Monserrat, Vilibić & Rabinovich 2006;Vilibić et al 2008;Goring 2009). Here it is shown that conditions for the occurrence of Proudman resonance and that suggested by V10 are modified in the presence of Coriolis effects.…”
Section: Introductionmentioning
confidence: 83%
“…Meteotsunamis are known to cause extensive damage and even loss of human life. The Balearic Island meteotsunami of 15 June 2006 with 5 m high waves caused economic loss of several tens of Correspondence to: J.Šepić (sepic@izor.hr) millions of euros (Jansa et al, 2007;Vilibić et al, 2008). The Nagasaki Bay meteotsunami of 31 March 1979, again with 5 m high waves, resulted in the drowning of three elderly women (Hibiya and Kajiura, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for bays and harbors with large amplification factors, which are prone to frequent meteotsunami events. A small change in the model coastline or depths can result in significant changes in eigen frequencies of the respective basin and maximum estimated wave-heights (Vilibić et al, 2008).…”
Section: Research Gaps and Perspectivesmentioning
confidence: 99%